1997
DOI: 10.1046/j.1365-3083.1997.d01-363.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Induction of Flavour Aversion in Mice. II. Passive/Adoptive Transfer and Pharmacological Inhibition

Abstract: Mice immunized with ovalbumin develop a strong aversion to ingesting sweetened egg white dilutions or ovalbumin solutions. In immunized animals, gavage or voluntary ingestion of ovalbumin triggers an increase of vascular permeability in the intestine; pretreatment with a mixture of histamine and serotonin antagonists blocked this reaction, but not the aversion; dexamethasone inhibited both the aversion and the increase in permeability. The aversion was transferred to normal recipient mice with high-titre anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
4
22
0
Order By: Relevance
“…The latter result suggests that there was an aversion to EWS by sensitized mice. This immunologically taste aversion was documented before (7,8) and was related to IgE responses (9). Recently, Basso and coworkers (17) have shown that after an oral Ova challenge, allergic mice presented higher levels of anxiety, increased Fos expression in emotionality related brain areas, and also aversion to Ova-containing solution.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The latter result suggests that there was an aversion to EWS by sensitized mice. This immunologically taste aversion was documented before (7,8) and was related to IgE responses (9). Recently, Basso and coworkers (17) have shown that after an oral Ova challenge, allergic mice presented higher levels of anxiety, increased Fos expression in emotionality related brain areas, and also aversion to Ova-containing solution.…”
Section: Discussionsupporting
confidence: 53%
“…We have reported that mice previously sensitized against ovalbumin (Ova) avoided the ingestion of a sweetened solution of egg white, choosing water instead (7,8), and this aversion was related to IgE antibodies (9). Indeed, elimination diet is still the mainstay of IgE-dependent food allergy therapy (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the immune reaction elicited by the ingestion of antigen (ovalbumin) leads to an increase in vascular permeability in the intestinal mucosa [3]; even when ovalbumin was given intravenously, an increase in vascular permeability was found in the stomach and small intestine [2].…”
Section: Introductionmentioning
confidence: 99%
“…The avoidance of voluntary ingestion of Ova-containing solutions by Ovaimmunized mice, the most sensitive clue of active immunization with low doses of protein, emerges between 10 and 14 days after primary immunization, concomitantly with the rise of detectable antibody titers in serum (18).…”
mentioning
confidence: 99%